Utilization of Tjilik Riwut Posters as Learning Media in Class IV Civics Learning at State Elementary School 3 Petuk Ketimpun - Ade Irma Suryani; Allyn Noviary; Andika Trisna; Karaya Nuril M. R.; Ady Ferdian Noor; Mahmud Mahmud; Noor Anita Ulfah; Revi Citra Dewi; M Fatchurahman; Iin Nurbudiyani (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
Aim: This research aims to describe the use of Tjilik Riwut poster media in civics learning for elementary school students. Method: The approach used in this research is qualitative with a descriptive type. The data collection technique is observation, unstructured interviews, and direct involvement in the development of this poster learning media. The subjects in this research were fourth grade students at SDN 3 Petuk Katimpun. The data analysis techniques used are data reduction, data presentation, and drawing conclusions. The research instrument is an observation sheet, to find out which is more effective, learning using poster media or regular learning using books and whiteboards. Conclusion: The conclusion is that poster media can build effectiveness in learning. Tjilik Riwut's poster media, which uses a projector, is considered effective and really helps better learning. Students generally like things they have never seen before. Class IV students, namely 15 students or 90% liked it and responded that learning using poster media was effective. Learning using poster media is very useful and teachers are very supportive because learning using poster media makes students happier and happier.